Hemodynamic events during en route critical care for patients with traumatic brain injury. (21st August 2022) - Davis, William T.; Medellin, Kimberly L.; Cutright, Julie E.; Arana, Allyson A.; Strilka, Richard; Sorensen, Derek; Maddry, Joseph K.; Savell, Shelia C.; Ng, Patrick C.
Abstract : The En Route Care Research Center abstracted charts from critical care air transport patients with TBI and found 14% in-flight prevalence of decreased blood pressure and 31% prevalence of decreased cerebral perfusion pressure among those with ICP monitoring. #CCATT #TBI #TCCC Abstract : BACKGROUND: Exposure to stressors of flight may increase risk of secondary insults among critically injured combat casualties wounded with traumatic brain injury (TBI). The primary objective of this study was to describe the prevalence of hemodynamic events by phase of transport among patients with TBI transported by Critical Care Air Transport Teams (CCATT). METHODS: We performed a secondary analysis of a retrospective cohort of 477 adults with moderate to severe TBI, who required transport by CCATT to Germany from multiple hospitals in the Middle East between January 2007 and May 2014. We abstracted clinical data from handwritten CCATT medical records. Hemodynamic events included systolic blood pressure <100 mm Hg and cerebral perfusion pressure <60 mm Hg. We calculated the proportion of patients experiencing hemodynamic events for each phase of flight. RESULTS: We analyzed 404 subjects after exclusions for catastrophic brain injury (n = 39) and missing timestamps (n = 34). Subjects had high Injury Severity Scores (median, 29; interquartile range [IQR], 21–35) and a median flight time of 423 minutes (IQR, 392.5–442.5 minutes). The median of documented in-flight vital signs was 8 measurements (IQR, 6.5–8 measurements). Documented systolic blood pressure in-flight events occurred in 3% of subjects during ascent, 7.9% during early flight, 7.7% during late flight, and 2.2% during descent, with an overall in-flight prevalence of 13.9%. Among patients with intracranial pressure monitoring (n = 120), documented cerebral perfusion pressure events occurred in 5% of subjects during ascent, 23% during early flight, 17% during late flight, and 5.8% during descent, with an overall in-flight prevalence of 30.8%. CONCLUSION: Documented hemodynamic events occurred during each phase of flight in severely injured combat casualties wounded with TBI, and episodic documentation likely underestimated the actual in-flight frequency of secondary insults. LEVEL OF EVIDENCE: Prognostic and epidemiological; Level IV. Abstract :